2016
DOI: 10.1186/s12915-016-0320-z
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated inhibition of C/EBP by Tribbles in multiple tissues is essential for Caenorhabditis elegans development

Abstract: BackgroundTribbles proteins are conserved pseudokinases that function to control kinase signalling and transcription in diverse biological processes. Abnormal function in human Tribbles has been implicated in a number of diseases including leukaemia, metabolic syndromes and cardiovascular diseases. Caenorhabditis elegans Tribbles NIPI-3 was previously shown to activate host defense upon infection by promoting the conserved PMK-1/p38 mitogen-activated protein kinase (MAPK) signalling pathway. Despite the promin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 57 publications
4
62
1
Order By: Relevance
“…On the other hand, only CEBP-1 expressed from ΔD2 transgene fully rescued the axon regeneration defect. Previous observations have revealed that cebp-1 acts in other dosage-dependent processes influencing larval development and axon regeneration (Kim et al, 2016, data not shown). These results indicate that the ability of the animal to tolerate changes in cebp-1 levels is minimal, and that precise control over cebp-1 levels may be accomplished by using multiple cis regulatory elements.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…On the other hand, only CEBP-1 expressed from ΔD2 transgene fully rescued the axon regeneration defect. Previous observations have revealed that cebp-1 acts in other dosage-dependent processes influencing larval development and axon regeneration (Kim et al, 2016, data not shown). These results indicate that the ability of the animal to tolerate changes in cebp-1 levels is minimal, and that precise control over cebp-1 levels may be accomplished by using multiple cis regulatory elements.…”
Section: Discussionmentioning
confidence: 78%
“…S1B). As cebp-1 is expressed in many tissues (Kim et al, 2016), to address 3′ UTR-mediated regulation specifically in the nervous system, we used the pan-neuronal rgef-1 promoter to drive transgene expression. We initially analyzed transgenic lines generated as high-copy extra-chromosomal arrays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These pseudokinases are thought to both link substrate binding to specific protein stability by recruiting ubiquitin ligases and as regulators of MAPK and AKT/FOXO - signaling (Eyers et al, 2016). There is one version of the trbl pseudokinase in Drosophila melanogaster and Caenorhabditis elegans (Kim, Thakur, Piggott, Omi, Polanowska, Jin, & Pujol, 2016; Mata, Curado, Ephrussi, & Rorth, 2000; Pujol, Cypowyj, Ziegler, Millet, Astrain, Goncharov, Jin, Chisholm, & Ewbank, 2008). Mouse and man have three, named trbl 1, 2, and 3 (Boudeau, Miranda-Saavedra, Barton, & Alessi, 2006; Eyers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%